A cross-sectional study to find out the prevalence of gastrectomy and identify complications with associated factors (in Iraqi patients aged (30-60 years) (Eurasian Medical Research Periodical, 2022)
This paper aims to find out the prevalence of gastrectomy and identify complications with associated factors (in Iraqi patients aged (30-60 years) A cross-sectional study was conducted for 90 patients between the ages of 30 to 60 years who underwent a gastrectomy procedure, where information and demographic data were collected from a number of different hospitals, and the data were analysed by relying on the IBM SOFT SPSS 18 program. As for the figures related to the results of this study were based on Microsoft Excel 2013